The First Episode Psychosis Services Fidelity Scale 1.0: Review and Update. Issue 1 (27th March 2021) - Addington, Donald
Abstract: The First Episode Psychosis Fidelity Scale, first published in 2016, is based on a list of essential components identified by systematic reviews and an international consensus process. The purpose of this paper was to present the FEPS-FS 1.0 version of the scale, review the results of studies that have examined the scale and provide an up-to-date review of evidence for each component and its rating. The First Episode Psychosis Services Fidelity Scale 1.0 has 35 components, which rate access and quality of health care delivered by early psychosis teams. Twenty-five components rate service components, and 15 components rate team functioning. Each component is rated on a 1–5 scale, and a rating of 4 is satisfactory. The service components describe services received by patients rather than staff activity. The fidelity rater completes ratings based on administrative data, health record review, and interviews. Fidelity raters from two multicenter studies provided feedback on the clarity and precision of component definitions and ratings. When administered by trained raters, the scale demonstrated good to excellent interrater reliability. The selection of components can be adjusted to rate programs serving patients with bipolar disorder or an attenuated psychosis syndrome. The scale can be used to assess and improve the quality of individual programs, compare programs and program networks. Researchers can use the scale as an outcome measure for implementation studies and as a process measure for outcome studies. Future research should focus on demonstrating predictive validity.